2002
DOI: 10.1097/01.mp.0000027625.79334.f5
|View full text |Cite
|
Sign up to set email alerts
|

Liposarcoma of the Oral and Salivary Gland Region: A Clinicopathologic Study of 18 Cases with Emphasis on Specific Sites, Morphologic Subtypes, and Clinical Outcome

Abstract: Liposarcoma is rare in the oral and salivary gland region (OSG), previously described in only case reports and two small series. Clinicopathologic features of a large series of these tumors were studied. Cases coded as "liposarcoma or lipoma" from 1970 to 2000 were searched for in our files. Inclusion required an OSG location and diagnosis by established soft tissue criteria. Dermal, other soft tissue, and intraosseous liposarcomas were excluded. Clinical and pathologic material was reviewed and follow-up obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
72
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 28 publications
9
72
0
Order By: Relevance
“…As has been shown in previous studies, head and neck liposarcomas [7,12] and intraoral liposarcomas [8][9][10] show a male predominance, in contrast to the reported female predilection for ALT/WDLS's of various locations [1,6,42]. The mean age of 64 patients with available information was 54.05 ± 17.84 years (age range 6 months to 86 years; median 54 years), with 78.1% of patients (50/64) being C40 years-old.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…As has been shown in previous studies, head and neck liposarcomas [7,12] and intraoral liposarcomas [8][9][10] show a male predominance, in contrast to the reported female predilection for ALT/WDLS's of various locations [1,6,42]. The mean age of 64 patients with available information was 54.05 ± 17.84 years (age range 6 months to 86 years; median 54 years), with 78.1% of patients (50/64) being C40 years-old.…”
Section: Discussionmentioning
confidence: 65%
“…Oral liposarcomas show a much lower incidence, as relevant reviews have reported a limited number of documented cases [8][9][10][11]. In a review of head and neck liposarcomas between 1911 and 2005, approximately 46% of cases (36/78) were localized in the oral mucosa [11], while oral and salivary gland liposarcomas accounted for only 0.3% (18/5,435) of all liposarcomas diagnosed in the Armed Forces Institute of Pathology between 1970 and 2000 [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among two series of non-lymphoid mesenchymal salivary neoplasms reported from large centers or registries, liposarcoma was represented by a single case in the two studies (one myxoid liposarcoma and one pleomorphic liposarcoma) [34,44]. However, the parotid gland was the third most common site for liposarcoma of the oral and salivary gland region in the AFIP series of 18 patients reported by Fanburg-Smith et al [45] Histological subtypes of the four patients included in this latter study were well differentiated/lipoma-like (2), myxoid (1) and dedifferentiated (1) liposarcoma [45]. Rare cases of liposarcoma metastatic to the parotid gland have been reported and should be included in the differential diagnosis of liposarcoma at this unusual location [46].…”
Section: Rare Lipoma Variantsmentioning
confidence: 99%
“…Also Japanese authors have presented data on the lack of prognostic relevance of low-versus high-grade DDLS [21], but again, none of these cases were located in the head and neck area. That liposarcomas of the head and neck region may carry a less sinister prognosis than in the retroperitoneum is suggested by a study by Fanburg-Smith et al [27] who presented a series of 18 cases of LS (including well differentiated, myxoid and dedifferentiated subtypes) where no patients developed metastasis or died of disease.…”
Section: Discussionmentioning
confidence: 99%